2020
DOI: 10.1186/s40792-020-00972-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal tubulopapillary neoplasms with rupture of the distal main pancreatic duct: a case report

Abstract: Background: Intraductal tubulopapillary neoplasm (ITPN) is a rare and newly described entity defined as an intraductal, grossly visible, tubule-forming epithelial neoplasm with high-grade dysplasia and ductal differentiation without overt production of mucin. Because of its rarity, the clinical and molecular aspects of ITPN have not been fully investigated. Case presentation: A 73-year-old woman presented to a local hospital with epigastric discomfort and pain. Abdominal multidetector-row computed tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…After applying our inclusion criteria, 68 articles were included in the systematic review (Figure S1). 11–78 …”
Section: Resultsmentioning
confidence: 99%
“…After applying our inclusion criteria, 68 articles were included in the systematic review (Figure S1). 11–78 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature review, four articles [ 3 , 5 , 12 , 13 ] mentioned 24 cases with a “two-tone-duct sign” (Table 1 ). Twenty-five percent (6/24 cases) showed a “two-tone-duct sign” and 87.5% (21/24) had an invasive component, out of which, 23.8% (5/21) showed the sign.…”
Section: Discussionmentioning
confidence: 99%
“…However, few cases have been diagnosed preoperatively. In some cases, surgery was performed with a suspicion of either pancreatic ductal adenocarcinoma (PDAC) or intraductal papillary mucinous neoplasm (IPMN) [3][4][5]. Some articles previously reported that the prognosis of ITPN is better than the conventional PDAC [6][7][8].…”
Section: Introductionmentioning
confidence: 99%